University of Florida Potato Variety Trials Spotlight: ‘Peter Wilcox’ - Rodrick Z. Mwatuwa; Christian T. Christensen; Pam Solano; Kathleen G. Haynes; Lincoln Zotarelli (EDIS)
by Rodrick Z. Mwatuwa, Christian T. Christensen, Pam Solano, Kathleen G. Haynes, and Lincoln Zotarelli http://edis.ifas.ufl.edu/hs1295